Stability of Anthocyanins and Their Degradation Products from Cabernet Sauvignon Red Wine under Gastrointestinal pH and Temperature Conditions - Yang, Ping (Molecules, 2018)
This study investigated the stability of wine anthocyanins under simulated gastrointestinal pH and temperature conditions, and further studied the evolution of anthocyanin degradation products through simulated digestive conditions. The aim of this study was to investigate the relation between anthocyanins’ structure and their digestive stability. Results showed that a total of 22 anthocyanins were identified in wine and most of these anthocyanins remained stable under simulated gastric digestion process. However, a dramatic concentration decrease happened to these anthocyanins during simulated intestinal digestion. The stability of anthocyanins in digestive process appeared to be related to their structure. The methoxy group in the B-ring enhanced the stability of anthocyanins, whereas hydroxyl group resulted in a reduction of their stability. Acylation decreased the stability of malvidin 3-O-glucoside. Pyruvic acid conjugation enhanced the structural stability of pyranoanthocyanins, whereas acetaldehyde attachment weakened their stability. A commercial malvidin 3-O-glucoside standard was used to investigate anthocyanin degradation products under simulated digestion process, and syringic acid, protocatechuic acid and vanillic acid were confirmed to be the degradation products via anthocyanin chalcone conversion path. Gallic acid, protocatechuic acid, vanillic acid, syringic acid, and p-coumaric acid in wine experienced a significant concentration decrease during digestion process. However, wine model solution revealed that phenolic acids remained stable under gastrointestinal conditions, except gallic acid.